2015
DOI: 10.4049/jimmunol.1402837
|View full text |Cite
|
Sign up to set email alerts
|

The Notch Signaling Pathway Controls Short-Lived Effector CD8+ T Cell Differentiation but Is Dispensable for Memory Generation

Abstract: Following an infection, naive CD8+ T cells expand and differentiate into two main populations of effectors: short-lived effector cells (SLECs) and memory precursor effector cells (MPECs). There is limited understanding of the molecular mechanism and cellular processes governing this cell fate. Notch is a key regulator of cell fate decision relevant in many immunological pathways. In this study, we add to the role of Notch in cell fate decision and demonstrate that the Notch signaling pathway controls the MPEC/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 62 publications
(103 reference statements)
2
43
0
Order By: Relevance
“…DLL1 and 4 induced development of Th1 cells and effector memory CD8 + T-cells (15,2529), whereas Jagged1 and 2 skewed T-cells into Th2, Treg, and anergic CD8 + T-populations (16,3033). In agreement with the proposed immune inhibitory role of Jagged, we found that anti-Jagged overcame tumor-T-cell suppression through the induction of potentially immunogenic MDSC-LC.…”
Section: Discussionmentioning
confidence: 99%
“…DLL1 and 4 induced development of Th1 cells and effector memory CD8 + T-cells (15,2529), whereas Jagged1 and 2 skewed T-cells into Th2, Treg, and anergic CD8 + T-populations (16,3033). In agreement with the proposed immune inhibitory role of Jagged, we found that anti-Jagged overcame tumor-T-cell suppression through the induction of potentially immunogenic MDSC-LC.…”
Section: Discussionmentioning
confidence: 99%
“…This was shown to be due to the growth effects of IL2 via PI3K signaling that triggers entry into the cell cycle ( Figure 1C). Additional crucial nodes of integration can be gleaned from recently reported studies: (i) Notch1 is activated by T cell signaling in cis, and additional Notch1/2 expression is triggered by IL2 signaling [26,53]. (ii) Further, TCR signaling induces digital expression of Myc, which is subsequently scaled by the level of IL2 signaling [54].…”
Section: Crosstalk With Il-2 Signaling For Collective Scalingmentioning
confidence: 98%
“…27,28 In addition, immunologists have pursued investigations into Notch’s role in multiple aspects of adaptive immunity. Thus, a multifaceted impact of Notch signaling on adaptive immunity has surfaced over the past decade, including identification of its enabling role in many arms of Th polarization (including Th1, 2933,34 Th2, 30,3539 Th9, 40 and Th17 41,42 ); its effects in terminal effector vs. memory precursor CD8 + T cell differentiation 4346 ; its effects on regulatory T cell function 47 ; and its synergy with B cell receptor signaling to promote class switching and terminal B cell differentiation and antibody production. 4850 How Notch mediates such a broad range of immune effects is progressively being elucidated.…”
Section: Notch Signaling In Adaptive Immunitymentioning
confidence: 99%
“…In infectious disease models (Listeria monocytogenes, Influenza), Notch activity was critical to ensure short-lived effector CD8 + T cell differentiation, in part due to direct regulation of Il2ra expression. 45,46 Upon Notch blockade, the acquisition of effector molecules (IFN-γ, Granzyme B, and Perforin) and the ultimate functional impact was variably affected in different models. 45,46 Data on the role of Notch signaling in CD8 + memory responses are more limited, however Notch appeared to favor effector CD8 + T cell responses over memory formation.…”
Section: Notch Signaling In Adaptive Immunitymentioning
confidence: 99%